2022
DOI: 10.3390/ijerph192315819
|View full text |Cite
|
Sign up to set email alerts
|

English Learning Stress, Self-Efficacy, and Burnout among Undergraduate Students: The Moderating Effect of Mindfulness and Gender

Abstract: Research has indicated that English learning stress contributes significantly to English learning burnout among undergraduate students. However, knowledge of the mediating and moderating mechanisms underlying this relationship is limited. To bridge this gap, a moderated mediation model was constructed to examine whether English learning self-efficacy mediated the relationship between English learning stress and English learning burnout. Furthermore, this study analyzed whether the mediated relationship was mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…Studies have found significant gender differences in English learning fatigue among college students, with females exhibiting greater proficiency in foreign language learning. Elevating the standards of English teaching in primary and secondary schools before higher education and encouraging and reinforcing language learning skills among male students may be beneficial (Xu et al, 2022).…”
Section: Mindfulness Meditation Training and The Effects On English L...mentioning
confidence: 99%
“…Studies have found significant gender differences in English learning fatigue among college students, with females exhibiting greater proficiency in foreign language learning. Elevating the standards of English teaching in primary and secondary schools before higher education and encouraging and reinforcing language learning skills among male students may be beneficial (Xu et al, 2022).…”
Section: Mindfulness Meditation Training and The Effects On English L...mentioning
confidence: 99%
“…Several studies have focused on examining the factors of burnout among students (Kaharudin et al, 2023;Mohd Shazali et al, 2023;Xu et al, 2022;Zhong & Liu et al, 2022;Zolkapli et al, 2023). These studies mainly relate to motivation and demotivation factors in investigating the causes of burnout which simultaneously affect language achievement negatively (Kaharudin et al, 2023;Mohd Shazali et al, 2023;Xu et al, 2022;Zhong & Liu et al, 2022;Zolkapli et al, 2023). The implications of these findings showed that the development of students' burnout in particular may correlate with gender and students' stress and self-efficacy on learning the language.…”
Section: Past Studies On Factors For Burnoutmentioning
confidence: 99%
“…In a recent study on factors of burnout, Xu et al (2022) constructed a moderated mediation model to study whether English language self-efficacy intervened in the interrelation of English learning stress and English learning burnout and if this intervened relation was impacted by gender and mindfulness of 1130 Chinese undergraduate students. The findings indicated that English learning self-efficacy significantly affected the relation of English learning burnout and English learning stress for both genders.…”
Section: Past Studies On Factors For Burnoutmentioning
confidence: 99%
“…Due to the fact that having a better proficiency in the English language requires students to have higher self-efficacy in performing various activities involving the language (Anam and Stracke, 2020), some researchers have found differences between men and women in terms of self-efficacy scores related to English achievement (Kutuk et al, 2022;Xu et al, 2022). For example, higher levels of self-efficacy for writing have been recorded for males compared to females (Ramos-Villagrasa et al, 2018); however, another study showed a stronger relationship between self-efficacy in writing and writing performance for female students than for male students (Pajares et al, 2001).…”
Section: Introductionmentioning
confidence: 99%